2014
DOI: 10.4062/biomolther.2014.040
|View full text |Cite
|
Sign up to set email alerts
|

Houttuynia cordata Improves Cognitive Deficits in Cholinergic Dysfunction Alzheimer’s Disease-Like Models

Abstract: Cognitive impairment is a result of dementia of diverse causes, such as cholinergic dysfunction and Alzheimer’s disease (AD). Houttuynia cordata Thunb. (Saururaceae) has long been used as a traditional herbal medicine. It has biological activities including protective effects against amyloid beta (Aβ) toxicity, via regulation of calcium homeostasis, in rat hippocampal cells. To extend previous reports, we investigated the effects of water extracts of H. cordata herb (HCW) on tauopathies, also involving calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 39 publications
2
33
0
1
Order By: Relevance
“…These data indicate that edaravone inhibits AChE and ChAT to modulate cholinergic dysfunction and improve cognitive deficits. Consistent with our results, recent studies suggested that the improvement of cognitive deficits was associated the inhibition of AChE in the mouse and rat models [15,16]. In addition, a recent study demonstrated that oxidative stress was involved in the cognitive impairment in AD [17].…”
Section: Discussionsupporting
confidence: 93%
“…These data indicate that edaravone inhibits AChE and ChAT to modulate cholinergic dysfunction and improve cognitive deficits. Consistent with our results, recent studies suggested that the improvement of cognitive deficits was associated the inhibition of AChE in the mouse and rat models [15,16]. In addition, a recent study demonstrated that oxidative stress was involved in the cognitive impairment in AD [17].…”
Section: Discussionsupporting
confidence: 93%
“…The characteristics of the maze have been described previously (Huh et al, 2014). This test is based on willingness of rodents to explore new environments.…”
Section: Y-mazementioning
confidence: 99%
“…After each trial the arms were cleaned with 20% ethanol to remove any residual odors. The results were expressed as described below: (Huh et al, 2014 …”
Section: Y-mazementioning
confidence: 99%
“…Results were expressed as percentage of novel object recognition time: Novel object recognition index¼ [(time of exploring novel object)/(time of exploring novel objectþtime of the familiar object)]  100. Y-maze test was carried out in a black three-arms with equal angles between all arms (40 cm  3 cm  12 cm) as previously described (Huh et al, 2014). An actual alternation was defined as entries into all three arms consecutively (i.e., ABC, CAB, or BAC but not ABA).…”
Section: Novel Object Recognition Test and Y-maze Testmentioning
confidence: 99%
“…Novel objective test (NORT) was carried out in a black open field box (45 cm  45 cm  50 cm) as previously described (Huh et al, 2014). Results were expressed as percentage of novel object recognition time: Novel object recognition index¼ [(time of exploring novel object)/(time of exploring novel objectþtime of the familiar object)]  100.…”
Section: Novel Object Recognition Test and Y-maze Testmentioning
confidence: 99%